2021
DOI: 10.3390/plants10112463
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Reserve Mobilization, Antioxidant Potential, and Expression Analysis of Starch Synthesis in Sorghum Seedlings under Salt Stress

Abstract: Salt stress is one of the major constraints affecting plant growth and agricultural productivity worldwide. Sorghum is a valuable food source and a potential model for studying and better understanding the salt stress mechanics in the cereals and obtaining a more comprehensive knowledge of their cellular responses. Herein, we examined the effects of salinity on reserve mobilization, antioxidant potential, and expression analysis of starch synthesis genes. Our findings show that germination percentage is advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The results of this experiment also agreed with the results of previous researchers of sorghum [22][23][24][25], and of maize [26,27]. Our results follow Rejili et al [28], who observed a decrease in the germination percentage of Lotus creticus that resulted from the osmotic effect of salts present in the growth medium.…”
Section: Germination Percentagesupporting
confidence: 92%
“…The results of this experiment also agreed with the results of previous researchers of sorghum [22][23][24][25], and of maize [26,27]. Our results follow Rejili et al [28], who observed a decrease in the germination percentage of Lotus creticus that resulted from the osmotic effect of salts present in the growth medium.…”
Section: Germination Percentagesupporting
confidence: 92%
“…The plasma membrane NHX exchange activity is considerably reduced in sos2-2 and sos3-1 mutants. Activated SOS2 can be added to membrane vesicle preparations in vitro to restore it to near-wild-type levels [108,109]. Regulation of Na + and K + ion homeostasis by the SOS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[102] in Wheat, and this was the mitigation of toxic effects by increasing the activity of antioxidants [16,[103][104][105][106][107]. Thus, how can explain why the experimental plants survived when using salicylic acid under higher concentrations of salinity and died at higher concentrations of salinity without using salicylic acid.…”
Section: Discussionmentioning
confidence: 99%